2015
DOI: 10.2135/cropsci2014.03.0201
|View full text |Cite
|
Sign up to set email alerts
|

Yield Response to Crop/Genotype Rotations and Fungicide Use to Manage Fusarium‐related Diseases

Abstract: Corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] cropping systems of the Midwest have led to increased selection pressure on diseases caused by Fusarium pathogens. A field experiment was conducted from 2010 to 2012 near Arlington, WI, to identify interactions among disease management practices (crop rotation, host resistance, and fungicide use) that increase corn, soybean, and wheat (Triticum aestivum L.) yields. For corn grain, significant interactions were primarily driven by crop rotation. Highest corn y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…A corn grain yield increase for CS, CSW, and CWS compared with CC has also been reported in several studies (Peterson and Varvel, 1989a, 1989b; Pedersen and Lauer, 2002, 2003; Gaudin et al, 2015; Mourtzinis et al, 2017). However, Marburger et al (2015a), in a previous 3‐yr study within the currently examined long‐term crop rotation experiment, found no yield difference between CC and CS rotations. Additionally, no corn grain yield benefit in the CSW rotation compared with CWS and CS in all 3 yr is in further agreement with Lund et al (1993).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A corn grain yield increase for CS, CSW, and CWS compared with CC has also been reported in several studies (Peterson and Varvel, 1989a, 1989b; Pedersen and Lauer, 2002, 2003; Gaudin et al, 2015; Mourtzinis et al, 2017). However, Marburger et al (2015a), in a previous 3‐yr study within the currently examined long‐term crop rotation experiment, found no yield difference between CC and CS rotations. Additionally, no corn grain yield benefit in the CSW rotation compared with CWS and CS in all 3 yr is in further agreement with Lund et al (1993).…”
Section: Resultsmentioning
confidence: 66%
“…In studies in Wisconsin and Nebraska, corn and soybean in rotation resulted in 18 and 38% greater corn yields and 13% greater soybean yields, respectively, than when grown continuously (Pedersen and Lauer, 2003; Peterson and Varvel, 1989a, 1989b). Similarly, a recent study reported an 8% yield increase for soybean grown in yearly rotation with corn in Wisconsin (Marburger et al, 2015a), whereas another study showed that yearly crop rotation increased yield of both corn and soybean when compared with continuous cropping by up to 20 and 22%, respectively (Mourtzinis et al, 2017).…”
mentioning
confidence: 99%
“…Our results agree with soybean yields reported in Iowa and Nebraska after 2 consecutive years of corn (Al‐Kaisi et al, 2016; Farmaha et al, 2016). In addition, several studies indicated that, in most situations, soybean grain yield was improved (+0.40 Mg ha −1 on average) when the C‐S rotation was diversified with winter wheat (Gaudin et al, 2015b; Marburger et al, 2015; Kazula and Lauer, 2018). However, Morrison et al (2018) did not observe any increase in soybean grain yield with a C‐S rotation that included spring wheat.…”
Section: Resultsmentioning
confidence: 99%
“…To examine interactions among multiple disease management practices, a comprehensive study was designed and implemented to meet two objectives: (i) identify possible combinations of practices which could reduce risk of disease development by decreasing Fusarium spp. populations (current study) and (ii) quantify the effect of combinations of these practices on yield (Marburger et al, 2014). This paper will focus on the first objective in which the effect of crop rotation and management (i.e., variety selection and fungicide use) on F. graminearum , F. oxysporum , and F. virguliforme populations in the soil was examined.…”
mentioning
confidence: 99%